INCORPORATING GAMIFICATION ELEMENTS FROM CLASSCRAFT IN ENGLISH INSTRUCTION: A SCOPING REVIEW - Armanda, Muhamad Laudy; Priyana, Joko (Sanata Dharma University, Yogyakarta, 2023)
In the contemporary educational landscape, a significant portion of college students belongs to Generation Z, characterized by their familiarity with the Internet, mobile technology, and video games. Educators are increasingly turning to innovative solutions to address the challenge of fostering a meaningful learning environment that enhances student motivation and improves learning outcomes. Classcraft, as a notable example, offers a platform for educators to captivate students through gamified learning experiences and immersive role-playing. This study conducts a scoping review to investigate research findings about the effectiveness of Classcraft, specifically focusing on its gamification elements, within the realm of English instruction. The review encompasses articles published between 2018 and 2023, following the comprehensive five-stage framework outlined by Arksey and O’Malley (2005). The key revelation of this scoping review underscores the advantages of integrating Classcraft to establish an immersive gamified learning environment in the context of English instruction. The insights derived from this review hold particular significance for instructional designers operating in higher education settings.